1947
DOI: 10.1021/ja01201a030
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Reaction of Alcohols with Thionyl Chloride1

Abstract: of carbon monoxide to increase from 0.26 at 15°t o 0.37 at 100°in the vapor phase vyhereas the yield in paraffin solution increased from 0.01 to 0.30 in the same temperature interval. The difference between the two cases may be due to the Franck-Rabinowitch effect. The yield of ethylene decreased in both cases with increase in temperature, but the change was not very pronounced. Thus the general phenomena in di-«-propyl ketone and in methyl «-butyl ketone are similar.The formation of acetone and propylene in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1953
1953
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 4 publications
(4 reference statements)
0
13
0
Order By: Relevance
“…Selectively deuterated samples of isopropylbenzene d 7 (deuterated chain), isopropylbenzene d s (deuterated ring) and perdeuterated isopropylbenzene were prepared according to the procedures described elsewhere [23][24][25]. All samples were degassed by the freeze-pump-thaw technique.…”
Section: Methodsmentioning
confidence: 99%
“…Selectively deuterated samples of isopropylbenzene d 7 (deuterated chain), isopropylbenzene d s (deuterated ring) and perdeuterated isopropylbenzene were prepared according to the procedures described elsewhere [23][24][25]. All samples were degassed by the freeze-pump-thaw technique.…”
Section: Methodsmentioning
confidence: 99%
“…Thionyl chloride is known to react with alcohols in the absence of hydrogen chloride acceptors to give reactions (2)- (7). Optimization of reactions (2) (7) and (4) is of primary concern in this section.…”
Section: A Reaction Of Thionyl Chloride With Alcoholsmentioning
confidence: 99%
“…The need for a hydrogen chloride acceptor was shown by Bissinger and Kung [7], who found that primary and secondary sulfites decompose to the halide if hydrogen chloride is not removed (Eq. 8).…”
Section: A Reaction Of Thionyl Chloride With Alcoholsmentioning
confidence: 99%
“…Thionyl chloride, phosphorus trichloride, and phosphorus tribromide are the most common examples of this group of reagents. [1][2][3][4][5] Thionyl chloride is often preferable to other reagents due to its gaseous byproduct (SO2) for simplified purification. 4 The excess of thionyl chloride can also be readily removed by distillation or evaporation.…”
Section: -Introductionmentioning
confidence: 99%
“…The reaction of alcohols with thionyl chloride initially results in the formation of a chlorosulfite ester which is transformed subsequently into the chloride (Scheme 1). [1][2][3][4][5][6] In the first stage, the alcohol attacks SOCl2 and after expulsion of Cland deprotonation, a chlorosulfite is formed. The mechanism for this stage is widely accepted and proceeds with retention of configuration at the carbon bearing the hydroxyl group.…”
Section: -Introductionmentioning
confidence: 99%